Needs Analysis for Developing Phonic Fun Congklak as a Digital-Traditional Game-Based Medium for English Vocabulary Pronunciation - Depi Prihamdani; Nurhaeda Gailea; Syafrizal Syafrizal; Tridays Repelita; Anggy Giri Prawiyogi (Journal of General Education and Humanities, 2026)
English pronunciation remains a challenge in Indonesian elementary schools because instruction is largely teacher-centred, supported by limited interactive media, and provides insufficient opportunities for repeated oral practice. Although previous studies have investigated gamification, multimedia learning, and traditional games, few have integrated these approaches through a comprehensive needs analysis as the basis for developing pronunciation learning media. This study aimed to analyze the instructional needs for developing Phonic Fun Congklak, a culturally responsive digital pronunciation learning medium. A qualitative descriptive needs-analysis design was employed during the Analysis stage of the ADDIE model. The participants were 3 English teachers and 36 Grade IV–V students from three public elementary schools in Karawang Regency, Indonesia. Data were collected through classroom observations, semi-structured interviews, curriculum document analysis, and media requirement analysis, and were analyzed thematically. The findings identified six key needs: linguistic, affective, pedagogical, media, curriculum, and cultural. These findings provide a strong foundation for developing Phonic Fun Congklak, which integrates phonics, authentic pronunciation audio, multimedia learning, gamification, and the traditional congklak game. The study contributes a needs-analysis framework to support the development of culturally responsive technology-enhanced pronunciation learning media for elementary school students.